In-situ synthesis of size-tunable silver sulfide nanoparticles to improve tribological properties of the polytetrafluoroethylene-based nanocomposite lubricating coatings. (August 2020) - Ma, Yanjun; Wan, Hongqi; Ye, Yinping; Chen, Lei; Li, Hongxuan; Zhou, Huidi; Chen, Jianmin
Abstract: Silver sulfide (Ag2 S) nanoparticles were prepared by in-situ method, and displayed the small size and good dispersibility in the lubricating coatings. A simple strategy was provided to regulate the size of the Ag2 S nanoparticles. The influences of Ag2 S nanoparticles and their sizes on the micro-hardness and tribological behaviours of the lubricating coatings were investigated, and the corresponding tribological mechanisms were discussed. Detailed investigation showed that the in-situ synthesized Ag2 S nanoparticles dominated by smaller-size and narrower size distribution increased the micro-hardness by 53.39% and reduced wear rate by 26.41%. The friction coefficient was independent to their size and size distribution. The superior tribological performance was attributed to the synergetic roles of the stronger micro-hardness and the high load-carrying tribofilm. Graphical abstract: Ag2 S nanoparticles with small size and good dispersion were in-situ synthesized in the PTFE-based nanocomposite lubricating coatings via the pyrolysis reaction of silver dialkyldithiocarbamate. A simple strategy by adjusting the substituted alkyl chain length of the single-source precursor was further provided to effectively control the size of the Ag2 S nanoparticles. Image 1 Highlights: Ag2 S nanoparticles with small size, good dispersion and narrow size distribution were synthesized in-situ. A simple strategy was provided to control the size of the Ag2 S nanoparticles. The Ag2 S nanoparticles greatly promoted the tribological properties of the lubricating coatings. The Ag2 S nanoparticles facilitated the formation of uniform tribofilm.